Point Targets, Tolerance Bands, or Target Ranges? Inflation Target Types and the Anchoring of Inflation Expectations - Michael Ehrmann (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Inflation targeting is implemented in different ways – most often by adopting point targets, by having tolerance bands around a point target, or by specifying target ranges. Using data for 20 economies, this paper tests whether the various target types affect the anchoring of inflation expectations at shorter horizons differently. It tests two contradictory hypotheses, namely that targets with intervals lead to (i) less anchoring, e.g. because they provide more flexibility to the central bank, or (ii) better anchoring, because they are missed less often, leading to an enhanced credibility. The evidence refutes the first hypothesis, and generally finds that target ranges or (in some cases) tolerance bands outperform the other types. However, the effects partially depend on the economic context and no target type consistently outperforms all others. This suggests that there are some benefits to adopting intervals, but the central bank can anchor inflation expectations also by other means.
Keywords: E52; E58; E31; 330; inflation targeting; inflation expectations; point target; tolerance band; target range